DO TRAINING REGIMEN AND COMPETITIVE LEVEL AFFECT BODY IMAGE DISSATISFACTION (LEANNESS AND MUSCLE TONE) IN FEMALE ATHLETES? - Fortes,Leonardo de Sousa (2019)
ABSTRACT Introduction Studies that seek analyze the relationship between sport variables and body image are importants, because indicate if the competitive sport environment influence on body feelings of athlete. Objective To analyze the relationship between sports variables (training regimen and competitive level) and dissatisfaction in regard to leanness and muscle tone in female athletes. Methods One hundred and eighty female athletes aged over 12 years from various sport disciplines participated in the study. We used the Body Shape Questionnaire (BSQ) to assess dissatisfaction in regard to leanness. The dissatisfaction subscale of Drive for Muscularity Scale (DMS) was used to evaluate dissatisfaction with muscle tone. Training regimen (frequency x daily hours of training) and competitive level were acquired through a questionnaire developed by the actual investigators. Results The findings indicated a statistically significant relationship between the training regimen (F(1, 179)=4.01; p=0.047) and competitive level (F(2, 178)=3.59; p=0.031) and the BSQ scores. Moreover, the results indicated a statistically significant relationship between the training regimen (F(1, 179)=4.01; p=0.047) and the competitive level (F(2, 178)=3.59; p=0.031), with DMS dissatisfaction subscale scores. Conclusion Sports variables (training regimen and competitive level) were related to dissatisfaction in regard to leanness and muscle tone, although they demonstrated different magnitudes. Level of evidence III; study case-control.